2005
DOI: 10.1128/jvi.79.21.13538-13547.2005
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoreceptors Reactivate Kaposi's Sarcoma-Associated Herpesvirus Lytic Replication via PKA-Dependent Control of Viral RTA

Abstract: Reactivation of Kaposi's sarcoma-associated herpesvirus (KSHV) lytic replication is mediated by the viral RTA transcription factor, but little is known about the physiological processes controlling its expression or activity. Links between autonomic nervous system activity and AIDS-associated Kaposi's sarcoma led us to examine the potential influence of catecholamine neurotransmitters. Physiological concentrations of epinephrine and norepinephrine efficiently reactivated lytic replication of KSHV in latently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 76 publications
(88 reference statements)
2
45
0
Order By: Relevance
“…Herpesviruses have also been shown to reactivate in response to stress and adrenergic stimuli (Bloom et al, 1997;Chang et al, 2005). For example, physiological concentrations of catecholamines have been demonstrated to induce lytic replication of HHV8 in latently infected lymphoid cells via badrenergic activation of cellular protein kinase A signaling pathway (Chang et al, 2005). These observations are in agreement with our findings of HHV8 DNA in a case of normal adrenal cortex adjacent to a pheochromocytoma and in two adrenocortical tumors, which were also positive for other herpesviruses.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Herpesviruses have also been shown to reactivate in response to stress and adrenergic stimuli (Bloom et al, 1997;Chang et al, 2005). For example, physiological concentrations of catecholamines have been demonstrated to induce lytic replication of HHV8 in latently infected lymphoid cells via badrenergic activation of cellular protein kinase A signaling pathway (Chang et al, 2005). These observations are in agreement with our findings of HHV8 DNA in a case of normal adrenal cortex adjacent to a pheochromocytoma and in two adrenocortical tumors, which were also positive for other herpesviruses.…”
supporting
confidence: 89%
“…However, glucocorticoids and/or other adrenal steroid hormones could indirectly activate viral replication through induction of expression of other transcription factors and coactivators that bind viralenhancer/promoter sequences and mediate glucocorticoid response. Herpesviruses have also been shown to reactivate in response to stress and adrenergic stimuli (Bloom et al, 1997;Chang et al, 2005). For example, physiological concentrations of catecholamines have been demonstrated to induce lytic replication of HHV8 in latently infected lymphoid cells via badrenergic activation of cellular protein kinase A signaling pathway (Chang et al, 2005).…”
mentioning
confidence: 99%
“…CREB1 has been implicated in regulating viral gene expression of a number of viruses, including hepatitis B virus (HBV) (29), herpes simplex virus 1 (HSV-1) (30), human cytomegalovirus (HCMV) (31), and human T-cell leukemia virus (HTLV) (32,33). A previous study showed that activation of the cAMP-dependent protein kinase A (cAMP/PKA) pathway, the classic CREB1 upstream pathway, is sufficient to reactivate KSHV from latency (34). However, it has been reported that KSHV infection of DMVEC is nonproductive, with minimal lytic activity (19), despite CREB1 activation via the cAMP/PKA pathway (35).…”
mentioning
confidence: 99%
“…This hypothesized link between innate antiviral responses and sympathetic denervation is particularly intriguing given recent indications that sympathetic neurotransmitters can inhibit innate antiviral responses (Collado-Hidalgo, et al, 2006). From this perspective, the localized sympathetic denervation observed here may serve to functionally de-repress Type I interferons (Collado-Hidalgo, et al, 2006) and withdraw catcholaminergic support for viral replication (Prosch, et al, 2000;Bloom, et al, 1994;Leib, et al, 1991;Willey, et al, 1984;Chang, et al, 2005;Turgeman and Aboud, 1998;Cole, et al, 1998;Cole, et al, 1999;Cole, et al, 2001;Sloan, et al, 2006). If true, this hypothesis implies that the dynamic denervation of lymphoid organs in response to viral infection may constitute a neurobiological component of the broader innate immune response to infection.…”
Section: Discussionmentioning
confidence: 99%